A New Method For Temperature Measurement To Determine The Temperature Variations In Cylindrical Grinding Contact Arc - Ms. Maya Madhukar Charde , Prof.Dr.Yogesh J Bhalerao (International Journal of Advanced Science and Technology, 2020)
Grinding of metals is a complex material removal operation. Research on cutting process of a single abrasive grain is the basis of further understanding of grinding mechanism. The cutting forces, the cutting temperature distribution and the strain rate in cutting zone are numerically demonstrated. The grinding process is the most suitable process to obtain a very good surface finish and accuracy. The objectives of this research paper are to investigate about the Face and Cylindrical Grinding Process.